Potential therapy of Sambiloto plant (Andrographis paniculata) using multi-compounds analysis - ., Handayani; Winarningsih, Wiwik (Gaceta Médica de Caracas, 2021)
Sambiloto plant (Andrographis paniculata) is often used as herbal medicine plant in Indonesia. Previous evidence indicates the use of a whole plant or single-compound approach. Analysis of multi-compounds is needed to determine the therapeutic potential for standardizing herbal medicine to provide a reliable effect. Methods: An exploratory study searching for the active content of A. paniculata was carried out in the Knapsack program.